A novel tunable inverted microstrip filter based on liquid crystal. Issue 7 (23rd April 2016) - Jiang, Di; Liu, Yupeng; Cao, Weiping; Chen, Hui; Luo, Wuqiong; Ding, Min
ABSTRACT: In this work, a microwave tunable filter of inverted microstrip with dual‐mode resonator using liquid crystal (LC) technology has been designed, manufactured, and characterized. It comprises a thin LC layer between a ground plane and a directly coupled and inverted microstrip line. Central frequency tunability was realised by applying low ac voltages, thus involving low power consumption. The transmission characters of the filter were specifically designed for working at C‐band microwave frequency range, which are allocated for many communication applications such as satellite, cordless telephone or weather radar systems. Additionally, its compact structure allows the device to be integrated on circuit board to adapt with other MW components for expanded applications. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1626–1628, 2016